Research Review on Teacher Emotion in Asia Between 1988 and 2017: Research Topics, Research Types, and Research Methods - Chen, Junjun (Frontiers in Psychology, 2019)
Background: Studies on teacher emotion have steadily become more prominent. However, it has been observed that scholarship on teacher emotion has been dominated by contributions from Western societies. In the absence of a critical mass of empirical research generated from within the region such as Asia, lack of knowledge and capacity to inform policy and practice in teacher education and evaluation mechanism. Methods: The current study sought to mirror the patterns of knowledge production in teacher emotion in terms of research topics, types, and methods and how they have evolved over time in Asia between 1989 and 2018. By using a descriptive quantitative analysis approach, we review a corpus of 154 articles on teacher emotion published in peer-review journals in Asia. It began with a systematic search in seven widely used electronic databases for abstracts of potentially relevant studies. Results: As observed, the trend represents a sea change in the volume of publications in Asia although the overall volume of research is still relatively low. Results also identify that although quantitative methods were most commonly used, the findings reveal a more balanced distribution since 1993. Furthermore, the use of qualitative and mixed methods of research has undergone a marked increase in the past 10 years. However, as the majority of articles were exploratory-oriented, intervention and experimental studies were largely lacking, which resulted in the ‘so-what' story being missing. Conclusions: A functionalist perspective suggests that knowledge production in teacher emotion research in Asia is either at the late first stage or the emerging second stage. Recommendations have been provided based on the major results and challenges.